Pengaruh Green Accounting, Intellectual Capital, dan Kinerja Keuangan Terhadap Nilai Perusahaan: Good Corporate Governance Sebagai Moderasi - Lelita, Renata Rosa; Hariyani, Diyah Santi; Wijaya, Anggita Langgeng (Universitas Muhammadiyah Ponorogo, 2024)
Research purposes for know influence Green Accounting, Intellectual Capital, and Performance Finance on Company Value with Good Corporate Governance as variable moderation. Research This done in the company mining sector energy listed on the IDX for the period 2019 – 2023. The data used is secondary data in the form of Annual Report and Sustainability Report period 2019-2023 accessed through www.idx.co.id as well as accessed from each company. Population study This own as many as 76 companies. The sampling technique sample use purposive sampling method so that obtained sample as many as 22 companies. The method used that is approach quantitative with use technique analysis multiple linear regression and moderated regression analysis (MRA). The data was processed with using the SPSS version 26 program. Research results This is Green Accounting has a significant negative effect on Company Value, Intellectual Capital has a significant positive effect on Company Value, Financial Performance has a significant negative effect on Company Value, Good Corporate Governance (GCG) can strengthen the relationship between Green Accounting and company value, Good Corporate Governance (GCG) cannot strengthen the relationship between Intellectual Capital and company value, Good Corporate Governance (GCG) can strengthen the relationship between Financial Performance and company value. Keywords: Green Accounting, Intellectual Capital, Financial Performance, Company Value, Good Corporate Governance.